Prevalence of restless legs syndrome in Trabzon in the northeast Black Sea Region of Turkey: co-morbidities, socioeconomic factors and biochemical parameters. (1st September 2015) - Altunayoglu Cakmak, Vildan; Koc, Bahattin; Nuhoglu, Irfan; Topbas, Murat; Yesilbas Ucuncu, Sehbal; Deger, Orhan; Kamburoglu, Sabiha; Velioglu, Sibel
Abstract: Objectives: Factors including heritability, climate features, co-morbid diseases and methodological differences between studies may underlie variation in the prevalence of restless legs syndrome (RLS). The purpose of this study was to assess the prevalence of RLS in Trabzon and to evaluate associated factors by including biochemical investigations. Methods: This community-based study was conducted among a random sample of 3789 adults. The criteria suggested by the International RLS Study Group were used in the assessment of RLS. Individuals responding affirmatively to at least one question were interviewed and examined by neurologists for definitive diagnosis of RLS. Age- and gender-matched RLS-negative individuals were enrolled in the control group. Blood samples from RLS patients and control subjects were collected after 12-hour fasting to evaluate fasting blood glucose, ferritin, vitamin B12, folic acid and creatinine. Results: The prevalence of RLS was 4.5%. Age, female gender and educational level were identified as independent risk factors for RLS. Peak prevalence rates were observed in the fourth decade in women and in the sixth decade in man. A familial history of RLS, low ferritin and vitamin B12 levels and multiparity were more common in women with RLS. Fasting blood glucose, folic acid and creatinine levels were not significantly different between the patients and controls. Discussion: The prevalence of RLS is relatively consistent in different regions of Turkey. Women with RLS may have different risk factors from men with RLS that may lead to increased prevalence at earlier ages. Low socioeconomic status may also affect the prevalence of RLS.